Nanoparticles for Use in Enzyme Assays. (19th January 2016) - Kim, Young‐Pil; Kim, Hak‐Sung
Abstract: Nanoparticles (NPs) have created new ways to enhance the performance of classical biosensors in analytical sciences. NPs with unprecedented physiochemical properties can serve both as excellent carriers of bioreceptors and as signal enhancers, leading to improved assay platforms with high sensitivity and selectivity. Because enzymes play central roles in many cellular functions, specific and precise assays of their functions are of great significance in medical science and biotechnology. Here we review recent advances in NP‐based biosensors and their use in enzyme assays. With fast and specific responses to enzyme‐mediated reactions, NPs transduce and amplify the initial responses into various types of signals, such as electrochemical, optical and magnetic ones. Translation of their potential should lead to functionalized NPs finding wide applications in diagnostics, drug development and biotechnology. Abstract : Improved biosensors for enzyme activity : Nanoparticles (NPs) make it possible to develop improved biosensors for the detection of enzyme activity. Whereas NPs serve both as excellent carriers of bioreceptors and as signal enhancers, NP‐based biosensors have evolved to achieve high sensitivity and selectivity. Here we review the recent advances in NP‐based biosensors and their applications to enzyme assays.